Trisomy 18 Pregnancies: Is there an Increased Maternal Risk? - Dotters-Katz, Sarah K.; Senz, Kayli L.; Humphrey, Whitney M.; Lee, Vanessa R.; Caughey, Aaron B. (American Journal of Perinatology, 2017)
Objective Characterize the impact of a trisomy 18 (T18) fetus on maternal and obstetric outcomes in a cohort including T18-affected deliveries. Study Design Retrospective cohort study of singleton deliveries in California from 2005 to 2008 using linked vital statistics and the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9) data to compare deliveries affected by T18 to those without known aneuploidy. Outcomes of interest included gestational diabetes mellitus (GDM), preterm delivery (PTD), preeclampsia, cesarean delivery (CD), and intrauterine fetal demise (IUFD). The χ2 and paired t-tests were used to compare the outcomes. Multiple logistic regression was used to further characterize these risks and control potential confounders. Results Of 2,029,000 deliveries, 298 involved T18. Compared with unaffected deliveries, T18 was associated with GDM (10.7 vs. 6.5%, p = 0.003), PTD < 37 (40.6 vs. 9.9%, p < 0.001) and < 32 weeks (14.8 vs. 1.4%, p < 0.001), and cesarean section (56 vs. 30.2%, p < 0.001), but not preeclampsia. In adjusted analyses, T18 pregnancies were associated with an increased risk of PTD < 37 and < 32 weeks (adjusted odds ratio [AOR]: 5.48, 95% confidence interval [CI]: 4.29, 6.99; AOR: 10.4, 95% CI: 7.26, 14.8), and an increased odd of CD for primiparous and multiparous women (AOR: 2.41, 95% CI: 1.48, 3.91; AOR: 5.42, 95% CI: 3.90, 7.53). Risk of GDM did not persist.Conclusion Unlike trisomy 13 (T13), pregnancies complicated by fetal T18 did not appear to result in an increased risk of preeclampsia. However, there is an increased risk of a range of other obstetric complications.
Keywords: trisomy 18; Edward's syndrome; maternal outcomes; preterm delivery; cesarean section